Comparison of MiniMed 780G system performance in users aged younger and older than 15 years: Evidence from 12 870 real‐world users. Issue 7 (12th May 2022) - Arrieta, Arcelia; Battelino, Tadej; Scaramuzza, Andrea E.; Da Silva, Julien; Castañeda, Javier; Cordero, Toni L.; Shin, John; Cohen, Ohad
Abstract: Aim: To investigate real‐world glycaemic outcomes and goals achieved by users of the MiniMed 780G advanced hybrid closed loop (AHCL) system aged younger and older than 15 years with type 1 diabetes (T1D). Materials and Methods: Data uploaded by MiniMed 780G system users from 27 August 2020 to 22 July 2021 were aggregated and retrospectively analysed based on self‐reported age (≤15 years and >15 years) for three cohorts: (a) post‐AHCL initiation, (b) 6‐month longitudinal post‐AHCL initiation and (c) pre‐ versus post‐AHCL initiation. Analyses included mean percentage of time spent in AHCL and at sensor glucose ranges, insulin delivered and the proportion of users achieving recommended glucose management indicator (GMI < 7.0%) and time in target range (TIR 70‐180 mg/dl > 70%) goals. Results: Users aged 15 years or younger (N = 3211) achieved a GMI of 6.8% ± 0.3% and TIR of 73.9% ± 8.7%, while spending 92.7% of time in AHCL. Users aged older than 15 years (N = 8874) achieved a GMI of 6.8% ± 0.4% and TIR of 76.5% ± 9.4% with 92.3% of time in AHCL. Time spent at less than 70 mg/dl was within the recommended target of less than 4% (3.2% and 2.3%, respectively). Similar outcomes were observed for each group (N = 790 and N = 1642, respectively) in the first month following AHCL initiation, and were sustained over the 6‐month observation period. Conclusions: This real‐world analysis shows that more than 75% of users with T1D aged 15 years or younger using the MiniMed 780G system achieved international consensus‐recommended glycaemic control, mirroring the achievements of the population aged older than 15 years.